The world's greatest war cartoonists and caricaturists, 1792-1945 - Bryant, Mark (Grub Street, 2011)
From the Napoleonic wars to World War II, this book introduces the political cartoonists, the opinion makers of peacetime and of wartime the world over. Here assembled are brief biographies of more than 300 of the most significant war cartoonists and caricaturists from the past three centuries. Artists from more than thirty countries are represented, from both sides of the wars concerned, whose artworks were published in newspapers, magazines, books, and as posters and postcards.--